Analisis Nilai Gotong Royong dalam Program Bank Sampah “Segar“ di Kelurahan Bendogerit Kota Blitar - Nurul Eka Fitria; Dwi Retnani Srinarwati; Riki Suliana RS (Universitas Palangka Raya, 2025)
Indonesia is experiencing an identity crisis that is seen from the fading values ​​such as the spirit of struggle, togetherness or mutual cooperation, concern, and unity. This study aims to describe how the value of mutual cooperation is applied between members of the management in the